2015
DOI: 10.2214/ajr.14.12683
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Transcatheter Arterial Embolization With N-Butyl-2-Cyanoacrylate for Control of Acute Gastrointestinal Tract Bleeding

Abstract: ing, renal arterial bleeding, and even gastrointestinal tract bleeding [2][3][4][5][6][7][8]. NBCA is highly penetrable because of its liquid nature and is less affected by coagulopathies; thus, it may be used as an adjunct to other embolic materials to ensure the embolic effect [9,10]. However, NBCA is difficult to handle effectively and safely and is inherently more prone to cause ischemic necrosis.Although there have been several reports on the use of TAE with NBCA for acute gastrointestinal tract bleeding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 35 publications
1
24
1
2
Order By: Relevance
“…TAE is generally regarded as a safe procedure with few complications. Indeed, Koo et al [5] reported a case series of 102 patients managed with TAE with a 76.5% success rate and 2 cases of ischemic complications. Two patients developed bowel infarction after TAE due to inadvertent embolization of adjacent, non-target vessels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TAE is generally regarded as a safe procedure with few complications. Indeed, Koo et al [5] reported a case series of 102 patients managed with TAE with a 76.5% success rate and 2 cases of ischemic complications. Two patients developed bowel infarction after TAE due to inadvertent embolization of adjacent, non-target vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, some NBCA might have overflowed into the ASPDA, suggesting that careless injection at a high speed or the use of an overdiluted NBCA mixture should be avoided to prevent overflow of the mixture into non-target vessels. Indeed, Koo et al [5] reported a case of duodenal infarction after extensive embolization of the ASPDA with NBCA. This patient died of septic shock due to duodenal perforation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Recently, n-butyl cyanoacrylate (NBCA) has been used as a liquid embolic agent in various non-traumatic situations, with a high technical success rate and low recurrent bleeding rate, particularly in patients with coagulopathy. 1,2) EVT using large-diameter catheter devices under anticoagulant therapy has become increasingly popular for the treatment of stroke. 3) Femoral vascular access-site complications are sometimes fatal and thus, initial resuscitation is a high priority for acute hemorrhage in hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 99%